2019
DOI: 10.4034/pboci.2019.191.115
|View full text |Cite
|
Sign up to set email alerts
|

Do Different Proportions of Antibiotics in the CTZ Paste Interfere with the Antimicrobial Action? In Vitro Study

Abstract: Objective: To evaluate the antimicrobial action of the CTZ paste in three different proportions by diffusion in agar with the microorganisms: Enterococcus faecalis, Escherichia coli, and Candida albicans. Material and Methods: Three different proportions of antibiotics were tested: GROUP A-CTZ paste in the ratio of 33.33% chloramphenicol + 33.33% tetracycline + 33.33% zinc oxide, mixed with 2 drops of eugenol (1:1:1 ratio); GROUP B-CTZ paste in the proportion of 25% chloramphenicol + 25% tetracycline + 50% zin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 14 publications
(19 reference statements)
2
5
0
2
Order By: Relevance
“…Studies evaluating the antimicrobial activity of CTZ paste against E. faecalis demonstrated inhibition of bacterial growth. 23,24,25 Our results also showed decreased CFU count for CTZ in the selective medium for E. faecalis. Colony growth of Candida spp.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…Studies evaluating the antimicrobial activity of CTZ paste against E. faecalis demonstrated inhibition of bacterial growth. 23,24,25 Our results also showed decreased CFU count for CTZ in the selective medium for E. faecalis. Colony growth of Candida spp.…”
Section: Discussionsupporting
confidence: 60%
“…This finding is consistent with previous results evaluated by tests such as agar diffusion. 3,22,25 In addition, the present study demonstrated, for the first time, the antimicrobial activity of CTZ on multispecies biofilms by direct contact with the paste.…”
Section: Discussionsupporting
confidence: 55%
“…There are few RCTs using the CTZ paste, but its antimicrobial capacity has been evaluated and proven in several in-vitro studies. 3,4,6,40 The great disadvantage of NIET with CTZ paste is the possible change in the color of the crown. 41 This browning is caused by the presence of tetracycline in the paste composition.…”
Section: Discussionmentioning
confidence: 99%
“…2 One of the most important aspects for successful treatment is the use of antimicrobial pastes. 3,4 Deciduous teeth have a distinct anatomy, with many accessory canals, irregular rhizolysis and great microbial diversity, making endodontic treatment problematic, 5 along with the presence of the permanent successor germ and the difficulty of managing child behavior due to the patient's young age. 2 Thus, it is essential to use obturation material with a broad spectrum of action, good diffusion, and that does not cause damage to periapical tissues and permanent teeth.…”
Section: Introductionmentioning
confidence: 99%
“…Os artigos foram realizados nos seguintes países: Brasil, Colômbia e México. Seis artigos foram estudos in vitro (Andrade, 2008;Piva;Faraco Junior;Estrela, 2008;Oliveira et al, 2019;Ern et al, 2020;Sancas et al, 2020), quatro artigos foram relatos de caso (Passos;Melo;Moreira, 2008;Moura et al, 2016;González-Núñez et al, 2010;Dias et al, 2021), avaliando apenas poucos pacientes, dois artigos foram estudos transversais (Moura et al, 2018;Sousa et al, 2020), avaliando uma grande quantidade de dentes decíduos, dois foram ensaio clínico randomizado (Luengo-Ferreira et al, 2016;Luengo-Ferreira et al 2019), com uma grande quantidade de molares decíduos avaliados, um artigo caracterizou-se como estudo retrospectivo Duarte, 2014), e um como estudo prospectivo (Carloto, 2020). O ano de publicação dos artigos variou de 2008 a 2021.…”
Section: Características Dos Estudos Incluídosunclassified